The Evidence of Different Learning Environment Learning Effects on Vocabulary Size and Reading Comprehension - Dong, Yang; Hu, Jieyi; Wu, Xiaoying; Zheng, Haoyuan; Peng, Xu (Frontiers in Psychology, 2018)
This longitudinal study has two aims. First to determine whether the mother language learning environment contribute more on second language learners’ vocabulary size and reading comprehension development. Second to discover whether single language learning results are better than double language, which means to test the hypothesis: the more information in environment, the better learning results. 170 high learning motivation middle school students completed the assessments of Raven IQ, entrance exam and vocabulary size test, all students were divided into 4 learning environment settings. One and half academic semester later, the assessment of vocabulary size and reading comprehension showed students single language learning environment got more scores in vocabulary size test and reading comprehension, and purely second language learning environment improve participants more on vocabulary size and reading comprehension than mother language learning.